Draft Annual Plan (2008-09) Statements Government of Puducherry - Planning Commission (Planning Commission, 2007)
Proposed Outlays - Major Heads / Minor Heads of Development, Proposed Outlays - Major Heads / Minor Heads of Development : From State Budget, State PSE’s and Local Bodies, Proposed Outlays - Major Heads / Minor Heads of Development - For Rural and Urban Local Bodies, Proposed Outlay on Continuing and New Schemes, Physical Targets and Achievements, Statement Regarding Externally Aided Projects, Bharat Nirman Programmes, Centrally Sponsored Schemes, Traibal Sub Plan (TSP): Financial Outlays, Tribal Sub Plan (TSP): Physical Targets and Achievements
Government of Puducherry, Planning and Research Department
Government of Puducherry, Planning and Research Department
Keywords: Proposed Outlays; Minor Heads of Development; Major Heads of Development; Physical Targets and Achievements; Bharat Nirman Programmes; Centrally Sponsored Schemes; Traibal Sub Plan (TSP); Women Component In The State Plan Programmes; Information Related To Industry Sector; Information Related To Transport Sector